Pengaruh Financing To Deposit Ratio (FDR) Terhadap Return On Asset (ROA) Dengan Variabel Intervening Penempatan Dana Pada Sertifikat Bank Indonesia Syariah (SBIS) Pada Bank Syariah di Indonesia - Al Ma'rifatul A'la; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to investigate the effect of Financing to Deposit Ratio (FDR) toward investment in Islamic Certificate of Bank Indonesia (SBIS), effect of investment in Islamic Certificate of Bank Indonesia (SBIS) toward Return on Asset (ROA), and effect of Financing to Deposit Ratio (FDR) toward Return on Asset (ROA) Islamic Bank in Indonesia.Methodology that used in this study is a quantitative approach. Technique analysis that used in this study is path analysis. Samples are used in this study collected from Islamic Bank Statistic Data issued by Bank Indonesia, January 2009 until October 2013, the total amount were 58 data.The results show that Financing to Deposit Ratio (FDR) has significantly negative effect on Islamic Certificate of Bank Indonesia (SBIS). Islamic Certificate of Bank Indonesia (SBIS) has not significantly effect on Return on Asset (ROA). Financing to Deposit Ratio (FDR) has significantly positive effect on Return on Asset (ROA). Financing to Deposit Ratio (FDR) with Islamic Certificate of Bank Indonesia (SBIS) as intervening variable have negative effect on Return on Asset (ROA) Islamic Bank in Indonesia. REFERENCESAnshori, Muslich dan Sri Iswati. 2009. Buku Ajar Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press.Arifin, Zainul. 2006. Dasar-dasar Manajemen Bank Syariah Edisi Revisi. Jakarta: Pustaka Alvabet.Chaudhry, Muhammad Sharif, Dr., M.A., LLB., Ph.D. 2012. Sistem Ekonomi Islam Prinsip Dasar. Jakarta: Kencana.Departemen Agama RI. 2004. Al-Qur’an dan Terjemahnya. Bandung: Syaamil Cipta Media.Fatwa Dewan Syariah Nasional No: 64/DSN-MUI/XII/2007 tentang Sertifikat Bank Indonesia Syariah Ju’alah (SBIS Ju’alah).Ginting, Ramlan dkk. 2013. Kodifikasi Peraturan Bank Indonesia Likuiditas Rupiah Operasi Moneter, Operasi Moneter Syariah dan Sertifikat Bank Indonesia Syariah. Jakarta: PRES Bank Indonesia.Greuning, Hennie Van dan Zamir Iqbal. 2011. Analisis Resiko Perbankan Syariah. Jakarta: Salemba Empat.Hidayat, Mohamad, MBA. 2010. An Introduction to The Sharia Economic Pengantar Ekonomi Islam. Jakarta: Zikrul Hakim.Ismal, Rifki. 2010. Assessment of Liquidity Management in Islamic Banking Industry. International Journal of Islamic and Middle Eastern Finance and Management, 3 (2):147-167.Machmud, Amir, Dr, dan Rukmana, H. S.E., M.Si. 2010. Bank Syariah Teori, Kebijakan, Studi Empiris di Indonesia. Jakarta: Erlangga.Muhamad. 2006. Teknik Perhitungan Bagi Hasil dan Profit Margin pada Bank Syariah. Yogyakarta: UII Press Yogyakarta (Anggota IKAPI).Muhammad, Dr. M.Ag. 2002. Manajemen Bank Syari’ah. Yogyakarta: UPP STIM YKPN.Muhammad. 2005. Manajemen Dana Bank Syriah. Yogyakarta: Ekonisia.Rivai, Veithzal dan Arviyan Arifin. 2010. Islamic Banking Sebuah Teori, Konsep, dan Aplikasi. Jakarta: Bumi Aksara.Soemitra, Andri, M.A. 2009. Bank dan Lembaga Keuangan Syariah. Jakarta: Kencana.Sugiyono, Prof. Dr. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&D. bandung: Alfabeta.Sumarsono, V. A. Ryan. 2012. Pengaruh Konflik Pekerjaan dan Konflik Keluarga terhadap Kinerja Karyawan Wanita dengan Konflik Pekerjaan-Keluarga sebagai Variabel Intervening di CV. Anugerah Motor. Skripsi tidak diterbitkan. Surabaya Fakultas Ekonomi dan Bisnis Universitas Airlangga.